Risk factors of ankle sprains and ankle injuries using mixed methods - Bestwick-Stevenson, Thomas (2024)
Background Ankle sprains are a common injury, in both the general population and physically active population. Residual symptoms are also common months and years after the injury, and many never fully recover. However, limited is known about the risk factors for suffering and recovering from an ankle sprain.